THE ROLE OF LAW ENFORCEMENT IN GOOD AND JUST LAW ENFORCEMENT AS SEEN FROM THE ASPECTS OF LEGAL SOCIOLOGY - Simon Adhirasi; Catharina Dewi Wulansari (CV. RADJA PUBLIKA, 2025)
Law is a set of rules containing norms and sanctions designed to regulate human behavior, create public order, and ensure justice. In this context, law can be used as a social engineering tool to regulate societal behavior. Law enforcement plays a crucial role in enforcing the law.Law enforcement is the most important factor in law enforcement efforts, as they are authorized by statutory regulations to undertake law enforcement efforts or a series of activities. This study addresses the impact of poor integrity among law enforcement officers and how to improve their integrity. The purpose of this study is to examine the impact of law enforcement officers lacking integrity in law enforcement and to provide solutions related to efforts that can be made to improve the integrity of law enforcement officers.